EKSTRAKSI DAN KARAKTERISASI KATEKIN DARI GAMBIR (Uncaria gambir roxb) - Isriza Mahendra; Minda Azhar (Departemen Kimia FMIPA UNP, 2022)
Gambir is the result of extraction from the gambier plant (Uncaria gambir roxb) where this plant contains polyphenolic compounds, namely catechins. Catechins are classified as flavanol compounds (flavon-3-ol) and are antioxidant compounds. The aim of the study was to determine the characteristics of the catechins extracted from gambier.Characterization of extracted catechins using FTIR showed characteristic absorption areas for the OH group at the peak of 3000-3700 cm-1 (3307), the C=C group around 1600 cm-1 (1607), and the CO group (1150-1010 cm-1) ( 1017). Characterization of extracted catechins using UV-Vis Spectrophotometer has a maximum wavelength of 290 nm. These characteristics are very similar to standard catechins.